Pengaruh Pemberian Mikroba Probiotik Lokal terhadap Peningkatan Produksi Jagung Hibrida - KARSIDI PERMADI (Agrotrop : Journal on Agriculture Science, 2013)
Local Probiotics Microbial Effect on Improvement of Hybrid Maize Production.Nationalmaize needs continue to increase every year, either for food, feed and industrial raw materials. To meetthis requirement Indonesia have to do import corn because the production at the farm level is still lowdue to poor application of resource integrated crop management (ICM) including the use of localprobiotic microbes.This study aims to determine the effect of applying maizeintegrated resourcemanagement ( ICM - maize ) using Local Probiotic Microbial fertilizer. The experiment was conductedin the village Cicurug, Majalengka Subdistricts, District Majalengka using a Randomized Block DesignComplete (RCBD), with four treatments and six replications. The treatment of local probiotic microbeswere: the dose of 3 l ha-1 Agri Simba, the dose of 3 l ha-1 Agri Simba + 1.500 g of urea, the dose of 6l ha-1 Agri Simba, and a dose of 6 l ha-1 Agri Simba + 3.000 g of urea. The results showed that the doseof applying local probiotic microbes (Agri Simba) has significant effect on growth, yield componentsand yield of hybrid maize varieties P-21.The highest yieldof dried shelled beans was 12.20 t ha-1achievedby the dose of 6 l ha-1Agri Simba+ 3.000 g urea.The lowest yield was 8.73 t ha-1 that obtained at doseof 3 l ha-1 Agri Simba. The componentsthat support tne yield of theP-21 hybrid maize wereweightofcob, number of rows per ear and weight of 100 grains.